Investigating Toxin Diversity and Abundance in Snake Venom Proteomes - Tasoulis, Theo; Pukala, Tara L.; Isbister, Geoffrey K. (Frontiers in Pharmacology, 2022)
Understanding snake venom proteomes is becoming increasingly important to understand snake venom biology, evolution and especially clinical effects of venoms and approached to antivenom development. To explore the current state of snake venom proteomics and transcriptomics we investigated venom proteomic methods, associations between methodological and biological variability and the diversity and abundance of protein families. We reviewed available studies on snake venom proteomes from September 2017 to April 2021. This included 63 studies characterising venom proteomes of 70 snake species, providing data on relative toxin abundance for 64 species and toxin diversity (number of different toxins) for 31 species. Methodologies utilised in these studies were summarised and compared. Several comparative studies showed that preliminary decomplexation of crude venom by chromatography leads to increased protein identification, as does the use of transcriptomics. Combining different methodological strategies in venomic approaches appears to maximize proteome coverage. 50% of studies used the RP-HPLC →1D SDS-PAGE →in-gel trypsin digestion → ESI -LC-MS/MS pathway. Protein quantification by MS1-based spectral intensity was used more commonly than MS2-based spectral counting. Total toxin diversity was 25-225 toxins/species, with a median of 48. The relative mean abundance of the four dominant protein families was for elapids; 3FTx– 52%, PLA2–27%, SVMP – 2.7%, and SVSP – 0.1%, and for vipers: 3FTx– 0.6%, PLA2– 26%, SVMP – 26%, and SVSP– 13%. Viper venoms were compositionally more complex than elapid venoms in terms of number of protein families making up most of the venom, in contrast, elapid venoms were made up of fewer, but more toxin diverse, protein families. No relationship was observed between relative toxin diversity and abundance. For equivalent comparisons to be made between studies, there is a need to clarify the best methodological approaches and for acceptance of a standardised protein classification, nomenclature and reporting procedure. Correctly measuring and comparing toxin diversity and abundance is essential for understanding biological, clinical and evolutionary implications of snake venom composition.